SWOT Analysis of Diaspora Engagement as An Influencing Factor in Albanian Economy - Milova, Olta; Vokshi, Arjeta (European Journal of Multidisciplinary Studies, 2022)
Emigration is constantly considered by Albanians as one of the main opportunities to improve their economic situation. Since in early times, history knows periods of massive immigration. In the last 30 years, there has been continuous emigration, but the period of massive departures was in the beginning and end of the 90s. There is a great interest and attention on immigrants and mainly long-term ones and their role in economic development, but there is still a gap of knowledge, data and indicators for quality policy-making, related to programs and tools that can facilitate participation and strengthen ties with immigrant communities. Why should an immigrant invest in his country? Their emigration has always been closely related to economic conditions, but not only. Economic emigration has influenced the continuous monetary flows to the other part of the family remaining in a country. The cultivation of this factor must be related to legal aspects, with dedicated strategies and other initiatives that institutionalize and facilitate the investment potential of the diaspora. However, there are many hindering factors, such as the political climate, frequent tax changes, differences in development between regions, etc. that prevent the connection of the diaspora with the country. This paper presents a detailed overview of favorable and hindering factors, strong and weak points that affect the absorption of investments from the diaspora in our country. The literature and studies review identify the main positive and negative factors that influence the economic decisions of emigrants or diaspora to invest in their homeland. The second part of the paper is dedicated to structured interviews directed to the main public institutions that implement strategies and policies for migration and diaspora, as well as being part of the plan of their measures. The factors identified through the interviews and the factors driven by literature and studies review are divided in strengths, weak, opportunities and threats in a SWOT analysis.